The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000021184
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of polydioxanone thread-embedding acupuncture (TEA) and electroacupuncture (EA) treatment for knee osteoarthritis (KOA) patients with postoperative pain

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Different wave types had different therapeutic effects, alternative waves can cause an inhibitory effect on motor nerves, with a good analgesic effect and lasting for a long time [13]. Previous studies [14][15][16] had shown that alternative waves could promote energy and metabolism, improved the flow of qi and blood, and had been widely used in the treatment of cervical spondylosis and other diseases [17,18]. One of the main features of Chinese medicine was syndrome differentiation and treatment, and naprapathy was a common Chinese rehabilitation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Different wave types had different therapeutic effects, alternative waves can cause an inhibitory effect on motor nerves, with a good analgesic effect and lasting for a long time [13]. Previous studies [14][15][16] had shown that alternative waves could promote energy and metabolism, improved the flow of qi and blood, and had been widely used in the treatment of cervical spondylosis and other diseases [17,18]. One of the main features of Chinese medicine was syndrome differentiation and treatment, and naprapathy was a common Chinese rehabilitation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2020 saw the burstness of the term “osteoarthritis”, indicating that in the last two years acupuncture analgesic techniques have started to be used in osteoarthritis surgery more often and intensive research has been conducted. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…2020 saw the burstness of the term "osteoarthritis", indicating that in the last two years acupuncture analgesic techniques have started to be used in osteoarthritis surgery more often and intensive research has been conducted. 47,48 The citation status of the references also manifests a distinctly evidence-based medical color. The most influential literatures in this field are of a variety which is dominated by RCTs and systematic reviews of clinical studies.…”
Section: Research Trends and Forefrontmentioning
confidence: 99%
“…In this study, the acupuncture points were selected to relieve pain in the knee joint as described in related previous studies. [7,19] Nine points were identified on the affected side: SP10, ST34, ST35, EX-LE5, SP9, GB34, GB33, ST36, and KI10. In case of pain in both knees, acupuncture points were considered from both sides.…”
Section: Experimental Group and Control Groupmentioning
confidence: 99%